The Effect of Giving Dynamic Stretching Active Isolated Stretchingand Nordic Exercise on Hamstring Muscle Flexibility in SSB Jayakarta Athletes - Indasah; Dwi Dimas Arrasyid; Hariyono (Journal Of Nursing Practice, 2025)
Background: Football is one of the most popular sports in society, sports injuries in early age soccer games can occur due to various things during training or during matches, such as physical training, techniques and tactics that are not programmed properly. Muscle flexibility plays a role as an important factor that influences the increased risk of injury. Muscle flexibility must be maintained in order to produce good flexibility. Purpose: The purpose of this study was to analyze the benefits of dynamic stretching, active isolated stretching and nordic exercise to improve hamstring muscle flexibility in SSB athletes. Methods: This study was conducted at the SSB Jayakarta soccer field, South Jakarta. This study was conducted for 6 weeks with a training intensity of 1 time a week in July 2024 - August 2024, with a sample of 36 SSB Jayakarta soccer players which is divided into 4 groups of 9 people each. The measuring instrument used to measure muscle flexibility is Active Knee Extension with Goneometer. Results: The results of the study in group I were p = 0.000, group II was p = 0.002 and group III was p = 0.000 using the paired samples t-test, indicating that all three interventions had an effect on increasing hamstring flexibility in SSB athletes. The ANOVA test showed a significant effect with a value (p <0.05) meaning there was a significant effect on the pre- post test. Conclusion: In conclusion, there was a significant difference between the Dynamic Stretching (K1) treatment group and the control group (K4), the Active Isolated Stretching (K2) treatment group and the control group (K4) and the Nordic Exercise (K3) with the control group (K4). However, in the Dynamic Stretching (K1), Active Isolated Stretching (K2) and Nordic Exercise (K3) treatment groups, there was no significant difference.